FACTORS INFLUENCING THE ADHERENCE TO ANTIDIABETICS AMONG ADULT DIABETIC PATIENTS ATTENDING THE DIABETIC CLINIC OF GOMBE HOSPITAL BUTAMBALA DISTRICT. A CROSS-SECTIONAL STUDY. - KUTEESA , NAKIWALA JEMIMAH (Student’s Journal of Health Research Africa, 2023)
Introduction: Objectives: The major objective was to determine factors affecting adherence to antidiabetic drugs among diabetic patients attending Gombe Hospital. Methodology: The research design was a cross-sectional study where quantitative approaches were used, the sample size was 86 patients, and was determined using Kish and Leslie formula. The sampling method used was random sampling. Data were analyzed using pencils, pens, and a calculator and then presented using figures, tables, and pie charts. Findings: 44(51.20%) reported that age affected their medication adherence 79 (91.86%) patients said that education levels did not affect their medication adherence. 58(67.4%) reported that the drugs pre- scribed to them were expensive. 56 (65%) respondents said that doctors took time to explain to them medication side effects and pill burden management. The majority of the respondents 52 (60%) said that most of the medications prescribed to them were not always available at the facility.58(67.4%) patients reported that it was discomforting to swallow the medication prescribed by the doctors. 58(67.40%) said that they visit the hospital once a month. Conclusions: The major health system-related factors affecting adherence were the availability of the prescribed medication in the hospital. In addition, taking a lot of pills a day lowered patients’ adherence and this could be improved by monotherapy. Economic status played a vital role in adherence to anti-diabetes medication for patients to afford the prescribed medication and that patient age played a role in patients’ adherence. Recommendations: Continuous education of the patients on the importance of adherence to diabetic medication whenever they go for clinic appointments. The government and partnering agencies should always ensure the timely supply of antidiabetic medicines to health facilities to facilitate easy accessibility and continuous availability of drugs to patients. Patients should visit hospitals regularly to avoid escalating complications due to reduced hospital reviews.